Analisis Kinerja Lalu Lintas Simpang Empat Tak Bersinyal di Jalan Raya Kepuharjo – Jalan Balai Desa Kepuharjo – Jalan Pertamanan Kecamatan Karangploso, Kabupaten Malang - Valdi, Didimus; Arifianto, Andy Kristafi; Rahma, Pamela Dinar (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2023)
At intersections there is often a conflict between opposing traffic flows and cutting each other off. One of the intersections that has a high level of congestion is the four unsignalized intersection at Jalan Raya Kepuharjo - Jalan Balai Desa Kepuharjo - Jalan Pertamanan Karangploso District Malang Regency. This study aims to determine the performance, and level of service at four unsignalized intersections on Jalan Raya Kepuharjo - Jalan Balai Desa Kepuharjo - Jalan Pertamanan Karangploso District, Malang Regency. This research uses quantitative and descriptive research types that are guided by PKJI 2014. The results of the study obtained the intersection performance obtained the results of the intersection capacity (C) of 26143 skr / hour, with a degree of saturation (DS) of 0.49, intersection delay (T) of 22.76 sec / sr and queuing opportunities that occur are 40.17% - 79.5%. The level of service obtained results of 0.49, with these results obtained the standard level of service type C (stable flow, increasingly limited speed), for the prediction of the level of service in the next five years DS 0.52, for the level of service C (stable flow, increasingly limited speed).